A2.30 TFH-like cells in the ra synovium are selectively associated with IL-21 production and ectopic lymphoid structures. (24th February 2016) - Lepse, N; Nerviani, A; Pitzalis, C; Bombardieri, M
Abstract : Background and objectives: A subset of rheumatoid arthritis (RA) patients are characterised by the presence of ectopic lymphoid structures (ELS) in the synovium. Synovial ELS display germinal centres with the in situ selection of ACPA-producing autoreactive B cells. T follicular helper (Tfh) cells play a critical role in germinal centre reactions in secondary lymphoid organs via expression of costimulatory molecules (eg, ICOS) and the release of IL-21, a potent B cell activator. Increased levels of IL-21 have been found in various autoimmune diseases and IL-21 is considered a potential therapeutic target in RA. The aim of this study was to characterise Tfh-like and IL-21-producing T cells in the RA synovium in the context of presence or absence of ELS. Materials and methods: RA synovial tissue was evaluated for the presence of Tfh-like cells (defined by co-expression of PD-1 and ICOS) by immunofluorescence microscopy. Synovial fluid mononuclear cells were either directly stained for surface marker expression or stimulated for 4h with Leukocyte Activation Cocktail in the presence of brefeldin A to evaluate cytokine expression by flow cytometry. IL-21 receptor (IL-21R) expression on fibroblast-like synoviocytes (FLS) was analysed by flow cytometry. Results: The numbers of PD-1+ICOS+ cells were significantly higher in ELS-positive than ELS-negative synovial tissue ([median ± SEM] 18.50 ± 9.6 vs 0.0 ± 1.4, p = 0.009). Consistent with the histological findings, increased percentages of CD4 + PD-1+ICOS+ cells (63.63%±17.21 vs 9.0%±1.8) and IL-21-producing CD4 + T cells were found in synovial fluid of arthritis patients when compared to peripheral blood of healthy donors ([median ± SEM] 19.53%±5.6 vs 5.43%±1.3). Furthermore, a sizeable subset of FLS (65.85%±16.92) expressed IL-21R and IL-21R mRNA expression in FLS could be significantly upregulated by TLR stimulation. Conclusions: Tfh-like cells are significantly more represented in ELS-positive than in ELS-negative synovium. IL-21-producing CD4 + T cells in synovial fluid might have a direct pro-inflammatory effect on FLS via IL-21/IL-21R signalling.